Amphiphilic Ruthenium(II) Terpyridine Sensitizers with Long Alkyl Chain Substituted β-Diketonato Ligands: An Efficient Coadsorbent-Free Dye-Sensitized Solar Cells - Ashraful Islam; Surya Prakash Singh; Masatoshi Yanagida; Mohammad Rezaul Karim; Liyuan Han (International Journal of Photoenergy)
Three alkyl-substituted β-diketonato-ruthenium(II)-polypyridyl sensitizers with different alkyl chain lengths, [Ru(tctpy)(tfpd)(NCS)] (A1), [Ru(tctpy)(tfdd)(NCS)] (A2), and [Ru(tctpy)(tfid)(NCS)] (A3), were designed and synthesized for dye-sensitized solar cells (DSCs) to investigate the effect of bulky alkyl chain substituents on the photovoltaic performances (where tctpy = 4,4′,4′′-tricarboxy-2,2′:;6′,2′′-terpyridine, tfpd =1,1,1-trifluoropentane-2,4-dione, tfdd = 1,1,1-trifluorodecane-2,4-dione, and tfid =1,1,1-trifluoroicosane-2,4-dione). These complexes exhibit a broad metal-to-ligand charge transfer absorption band over the whole visible range extending up to 950 nm. All complexes were examined in the presence and absence of the coadsorbent deoxycholic acid (DCA) in dye-bath solutions. These sensitizers, when anchored to nanocrystalline TiO2 films, achieve efficient sensitization to TiO2 electrodes. Under standard AM 1.5 sunlight, the complex A3 containing long alkyl chain length of C16 yielded a short-circuit photocurrent density of 18.0 mA/cm2, an open-circuit voltage of 0.64 V, and a fill factor of 0.66, corresponding to an overall conversion efficiency of 7.6% in the absence of DCA. The power conversion efficiency of A1 sensitized DSCs was significantly increased upon the addition of DCA as compared to that in the absence of DCA. However, the photovoltaic performance of A3 was not dependent on DCA at all, probably due to the inherent structural nature of the A3 molecule.